The Educational Implications Derived from the Hadith of the Ten Noble Morals and Their Effects on the Individual and Society - Hassoun, Prof. Dr. Odai Musab Hassoun; Mujbil, Prof. Dr. Mahmoud Hameed Mujbil (Sulaimani Journal for Humanities, 2026)
The research aims to extract the educational implications from the Hadith “The virtues of good character are ten” and to highlight their impact on both the individual and society. It focuses on the moral values reinforced by the Hadith and their role in shaping an upright personality and a cohesive community. Topical Scope: The study is limited to the Hadith “The virtues of good character are ten” and the analysis of its educational content. Methodological Scope: The analytical and deductive method was adopted.
Keywords: Virtues of Good Character; Educational Implications; and Islamic Education